METODE PEMBELAJARAN HAFALAN SURAT PENDEK PADA BIDANG STUDI AL-QUR’AN HADITS PADA SISWA MADRASAH IBTIDAIYAH NEGERI (MIN) JATI KAMPUNG BARU KECAMATAN KAMANG MAGEK KABUPATEN AGAM - Janewar; M. Yemmardotillah (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2019)
Implementation of strategies in the teaching process is strongly influenced by the quality of teachers in the mastery of learning theories. Very many and varied methods in teaching and learning that can be used by teachers in the implementation of learning. Subjects in the study of the Koran Hadith, especially on the matter of rote short letter, a strategy that can be implemented by teachers is the use of peer tutoring, assignments and so forth. Just as the State Islamic Elementary School (MIN) Kampung Jati Baru Agam district, teachers have attempted to implement various strategies in the implementation of learning, but the efforts undertaken by the teacher. The purpose of this study was to determine the efforts of teachers in the preparation, implementation, evaluation and supporting and inhibiting factors for teachers in applying the method of rote learning in a short letter to the material Subjects Qur'an Hadith in Kampung Jati Baru MIN. So expect the study to be a reference to enhance the rote learning method, especially in the Qur'an.